Film Analysis: Obsessive compulsive disorder and bipolarity in the characters of the movie Silver Lining Playbook (Research, Society and Development, 2020)
The present study aimed to discuss bipolarity, obsessive compulsive disorder (OCD) and, briefly about sexual compulsion, pathologies identified in some of the characters of the cinematic narrative “The good side of life” (2012). This is a study of narrative review of the literature, carried out over a period of one month in 2019, in which articles, books and epidemiological bulletins were used that covered the delimited subject. It was identified as main results, that the risk factors that cause OCD and bipolarity contemplate issues that are not only psychological, but also biological and physiological. It is concluded that in addition to the techniques usually used to treat and control these psychopathologies, art is of great importance during the therapeutic process, providing greater control of symptoms.